Penerapan pakan yang mengandung kunyit pada budidaya ikan lele di Kelurahan Sukamaju Kecamatan Sail, Pekanbaru - Morina Riauwaty; Yusni I Siregar; Isma Muyani; Indra Lesmana (Unri Conference Series: Community Engagement, 2020)
Sukamaju Village that is located in the Sail Sub Regency, Pekanbaru is potential for developing fish culture. The knowedge of the community in fish culturing method, however, is relatively low and to improve it, a socialization program has been conducted in July-September 2020. The community was trained to culture fish and fed the fish with turmeric enriched pellets through mentorial and practice in fish feed pellet manufacture and fish rearing. The progress was monitored weekly and evaluated by the 8th week. Results shown that the community was able make fish feed pellets and also able to culture the fish. The result of monitoring and evaluation shown that the fish farmer in Sukamaju Village is commited to develop the turmeric enriched fish fed pellet processing as the effort of program sustanability.